Penetrasi Dakwah Islamisme Eks HTI di Indonesia:: Studi Netnografi Dakwah Felix Siauw & “Yuk Ngaji” di Media Sosial - As'ad, SettingsMuhammad (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2021)
This article seeks to answer a question on how the da’wah activities of former members of Hizbut Tahrir Indonesia (HTI) conducted after its disbandment in 2017. This study used a qualitative method with netnography approach in which participation observation is conducted primarily online. The sample of this research was the social media account of former HTI activist, Felix Siauw and his da’wah team of “Yuk Ngaji”. Findings illustrate that the online da’wah of former HTI members has remained a quite strong and omnipresent on the internet that has similar vision to HTI in which their da’wah activities offer khilafah doctrine. Both Felix Siauw and team of “Yuk Ngaji” utilise the method of da’wah 2.0 which is maximizing visual aesthetics, communication skills, and marketing strategies. As the result, they are quite successful in attracting the millennials to be part of their da’wah movement.